2008
DOI: 10.1590/s1676-06032008000300011
|View full text |Cite
|
Sign up to set email alerts
|

Richness, abundance, and mass in snake assemblages from two Atlantic Rainforest sites (Ilha do Cardoso, São Paulo) with differences in environmental productivity

Abstract: . 2008. Richness, abundance, and mass in snake assemblages from two Atlantic Rainforest sites (Ilha do Cardoso, São Paulo) with differences in environmental productivity. Biota Neotrop. 8(3): http://www.biotaneotropica. org.br/v8n3/en/abstract?article+bn01408032008. Abstract:We analyzed richness, composition and mass of snakes in two sites in the Atlantic forest of Ilha do Cardoso (25° 03' S and 47° 53' W), an island (22,500 ha), Cananéia municipality, São Paulo State, Brazil. A monthly index of arthropod avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
12
0
3
Order By: Relevance
“…For the species discussed here, many have ecological and medical importance (ROCHA et al 2008), which evidences the necessity to know the local fauna. The present study contributes to the knowledge about the snake assemblage in the west of Minas Gerais (Ituiutaba region), and sheds light on the need of future studies on diversity and distribution of this vertebrate group in the Cerrado under an unfavorable scenario with respect to conservation of natural areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the species discussed here, many have ecological and medical importance (ROCHA et al 2008), which evidences the necessity to know the local fauna. The present study contributes to the knowledge about the snake assemblage in the west of Minas Gerais (Ituiutaba region), and sheds light on the need of future studies on diversity and distribution of this vertebrate group in the Cerrado under an unfavorable scenario with respect to conservation of natural areas.…”
Section: Discussionmentioning
confidence: 99%
“…This group has great ecological significance and the consequences of diversity loss can be severe, because as predators, they contribute to prey population control (ROCHA et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Areas used for the analysis of similarity between snake assemblages.The following snake assemblages were included in the analyzes: São Paulo State: 1 Parque Estadual Turístico do Alto Ribeira (Araújo et al 2010) 2 Ilha da Cananéia (Cicchi et al 2007) 3 Parque Estadual Ilha do Cardoso (Rocha et al 2008) 4 Fazenda Etá (Fiorillo 2016) 5 Ilha Comprida (Cicchi et al 2007) 6 Estação Ecológica Juréia-Itatins (Marques and Sazima 2004) 7 Parque Estadual Carlos Botelho (Forlani et al 2010) 8 Municipalities of Tapiraí and Piedade (Condez et al 2009) 9 São Sebastião (Centeno et al 2008) 10 Ilhabela (Centeno et al 2008) 11 Parque Municipal de Paranapiacaba (Trevine et al 2014) 12 São Paulo (Barbo et al 2011) 13 Parque Estadual da Serra do Japi (Sazima and Haddad 1992) 14 São Vicente Island (Cicchi et al 2007) 15 Santo Amaro Island (Cicchi et al 2007) 16 Parque Estadual da Serra do Mar (Núcleo Santa Virgínia) (Hartmann et al 2009a) 17 Parque Estadual da Serra do Mar (Núcleo Picinguaba) (Hartmann et al 2009b) 18 São José do Barreiro (Ortiz et al 2017); Rio de Janeiro State 19 Ilha Grande (Rocha and Van-Sluys 2006) 20 Parque Natural Municipal da Serra do Mendanha (Pontes et al 2009) 21 Duque de Caxias (Salles and Silva-Soares 2010) 22 Niterói (Citeli et al 2016) 23 Estação Ecológica do Paraíso (Vrcibradic et al 2011) 24 Núcleo Experimental de Iguaba Grande (Martins et al 2012) Minas Gerais State 25 Munhoz (Cardoso 2011) 26 Parque Estadual da Serra do Papagaio (This study) 27 Parque Estadual da Serra do Brigadeiro (Moura et al 2012) 28 Viçosa (Costa et al 2010) 29 Ouro Branco (São-Pedro and Pires 2009) 30 Ouro Preto and surroundings (Silveira et al 2010) 31 Estação Ambiental de Peti (Bertoluci et al 2009). …”
Section: Methodsunclassified
“…Such richness is much less than that found in different regions of the Amazonia (e.g., Dixon and Soini 1977 [88 Martins and Oliveira 1998 [66 species]), in the Brazilian Cerrado (Sawaya et al 2008 [36 species], Araujo et al 2010 [21 species]), and is less than that reported in the Colombian Pacific lowlands (Moreno et al 2003 [25 species]), and in one locality at the Cordillera Occidental (Castro-Herrera et al 2007 [22 species]). However, different environmental factors such as climate, topography, landscape configuration and environmental productivity, besides the factors associated with the type of sampling and data collection, can directly influence the diversity patterns observed in Manizales (see Rocha et al 2008, Sawaya et al 2008, UrbinaCardona et al 2008. Therefore, making comparisons of species diversity is extremely complicated when related to dissimilar environmental areas, and when different sampling methods have been used (Feisinger 2001).…”
Section: Richness and Compositionmentioning
confidence: 99%